Non-invasive measurement of cortisol metabolites in feces as an indicator of stress and its relationship with the number and arrival frequency of visitors in captive sambar deer (Cervus unicolor). Issue 1 (May 2021) - Gholib, G; Jannah, P T M; Wahyuni, S; Rahmi, E; Hanafiah, M; Adam, M
Abstract: Nowadays, the non-invasive measurement of cortisol in feces is a popular method used as an indicator of stress in wild and captive animals. This study was conducted to examine the feasibility of a non-invasive method for cortisol metabolites measurements in feces and investigate its relationship with the number and arrival frequency of visitors in captive Sambar deer. In total 64 fecal samples were collected together with the observation of the number and arrival frequency of visitors from 7 Sambar deers (3 adult males, 4 adult females) rearing in zoos of Taman Rusa Lamtanjong, Aceh Besar, Indonesia. Subsequently, fecal samples were extracted and the concentration of cortisol was measured by using 3α, 11β-dihydroxy-etiocholanolone assay. Data were analyzed using a t-test and Pearson correlation. Results showed that cortisol metabolites concentration in adult males of Sambar deer (276.20 ± 52.74 ng/g dry feces) was higher compared to adult females (181.56 ± 25.87 ng/g dry feces). The concentration of cortisol metabolites was significantly correlated with the number of visitors ( r = 0.482, p < 0.05 ) and the arrival frequency of visitors ( r = 0.398, p < 0.05 ) in which the higher number and arrival frequency of visitors increased the cortisol metabolites concentration. In conclusion, the concentration of cortisol metabolites in Sambar deer can be measured non-invasively from feces and associated with the number and arrival frequency of visitors.